Some Natural Plant Extracts can be used as Leishmania Stains - Nidaa Mohammed Sulaiman (Journal of Global Pharma Technology, 2018)
Visceral leishmaniasi is a chronic disease caused by Leishmania donovani. Staining method is an effective way for identification of parasites by using synthetic or natural dyes. In this study Morus nigra, Punica granatum and Quercus infectoria extracts were used as natural dyes to investigate their staining activity to stain L. donovani promastigote in comparison with geimsa stain. Results: the three extracts showed a good staining ability, M.nigra was the best followed by P. granatum and Q. infectoria. Conclusion: according to the results, dying with natural dyes is cheap, safe and could be alternative for synthetic dyes.                                   Keywords: Natural dyes, Synthetic dyes, L. donovani, Extrac.